MODELING OF REAL COMBAT OPERATIONS - Kostić, Mladen; Jovanović, Aca (Journal of process management and new technologies, 2023)
This paper discusses the model of an offensive air-ground combat operation, a product of a specific modeling - operational planning and targeting process. The modeling was performed using approximate methods of numerical integration based on Lanchester's law of combat. Operational factors and their implications for outcome are used for modeling a spetial but still current, offensive air-ground campaign/operation "Desert Storm". The model considers relevant factors, such as combat capabilities, the number of forces and consumption of resources and forces attrition in combat, in order to enable planning and prediction of the winning side in battle. The optimal solution of the problem as a useful strategic tool, based on the attrition model of combat has a practical benefit for making the right management decisions in operational planning process. This approach corresponds to project management, considering the same operational factors and the ability to manage them
Keywords: Force attrition; combat operations; approximateive model